Distinctive Archaeal Composition of an Artisanal Crystallizer Pond and Functional Insights Into Salt-Saturated Hypersaline Environment Adaptation - Plominsky, Alvaro M.; Henríquez-Castillo, Carlos; Delherbe, Nathalie; Podell, Sheila; Ramirez-Flandes, Salvador; Ugalde, Juan A.; Santibañez, Juan F.; van den Engh, Ger; Hanselmann, Kurt; Ulloa, Osvaldo; De la Iglesia, Rodrigo; Allen, Eric E.; et al. (Frontiers in Microbiology, 2018)
Hypersaline environments represent some of the most challenging settings for life on Earth. Extremely halophilic microorganisms have been selected to colonize and thrive in these extreme environments by virtue of a broad spectrum of adaptations to counter high salinity and osmotic stress. Although there is substantial data on microbial taxonomic diversity in these challenging ecosystems and their primary osmoadaptation mechanisms, less is known about how hypersaline environments shape the genomes of microbial inhabitants at the functional level. In this study, we analyzed the microbial communities in five ponds along the discontinuous salinity gradient from brackish to salt-saturated environments and sequenced the metagenome of the salt (halite) precipitation pond in the artisanal Cáhuil Solar Saltern system. We combined field measurements with spectrophotometric pigment analysis and flow cytometry to characterize the microbial ecology of the pond ecosystems, including primary producers and applied metagenomic sequencing for analysis of archaeal and bacterial taxonomic and functional diversity of the salt crystallizer harvest pond. Comparative metagenomic analysis of the Cáhuil salt crystallizer pond against microbial communities from other salt-saturated aquatic environments revealed a dominance of the archaeal genus Halorubrum and showed an unexpectedly low abundance of Haloquadratum in the Cáhuil system. Functional comparison of 26 hypersaline microbial metagenomes revealed a high proportion of sequences associated with nucleotide excision repair, helicases, replication and restriction-methylation systems in all of them. Moreover, we found distinctive functional signatures between the microbial communities from salt-saturated (>30% [w/v] total salinity) compared to sub-saturated hypersaline environments mainly due to a higher representation of sequences related to replication, recombination and DNA repair in the former. The current study expands our understanding of the diversity and distribution of halophilic microbial populations inhabiting salt-saturated habitats and the functional attributes that sustain them.